Printability of a Cellulose Derivative for Extrusion-Based 3D Printing: The Application on a Biodegradable Support Material - Cheng, Yiliang; Shi, Xiaolei; Jiang, Xuepeng; Wang, Xiaohui; Qin, Hantang (Frontiers in Materials, 2020)
Support material plays a leading role in the application of 3D printing to avoid deformation and enhance stability. This study aimed to fabricate the support structure by using hydroxypropyl methylcellulose (HPMC), which has advantages over conventional material such as low cost, low printable temperature, and high biodegradability. Once dissolved in water over gelling temperature, the HPMC based hydrogel exhibited shear-thinning behavior with decreasing apparent viscosity values at higher shear rates. The shear-dependent viscosity makes the HPMC hydrogel extrudable throughout the printing process and the printed structure stable enough without deformation. As concentration increased, apparent viscosity and storage modulus both subsequently increased. These rheological properties indicated that the concentration of HPMC K4M hydrogel significantly influenced the printability and shape retention ability, which is associated with the mechanical strength of printed filaments. The highest concentration, 12% w/v, should have the best ability to hold the printed shape over time due to the highest G' and lowest loss tangent. The printability test also showed that K4M 12% w/v could be printed into different fill density (100%, 75%, and 50%) with different patterns, i.e., rectilinear and Hilbert curve. The selection of fill density and pattern both have an effect on surface roughness and porosity. The printed support material was compatible with acrylonitrile butadiene styrene (ABS), which is the material to fabricate the main structure for 3D printing. The support material made of HPMC can be easily removed by peeling off from the main structure without visible residual.